2014
DOI: 10.1039/c4cc06648k
|View full text |Cite
|
Sign up to set email alerts
|

A porous metal–organic framework with –COOH groups for highly efficient pollutant removal

Abstract: A new metal-organic framework with -COOH groups has been realized and demonstrates strong interactions with methylene blue and thus the complete removal of methylene blue from aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 46 publications
3
63
0
Order By: Relevance
“…Obviously, MOFs 1 and 2 show much more superior adsorption capacity over MB by about three times that of 3 and 4 in terms of the unit mass of the adsorbent due to the lower atomic weight of Mg/Ca (in 1 / 2 ) in comparison with that of Sr/Ba (in 3 / 4 ). In addition, the electrostatic interaction of nitrogen atoms of porphyrin remained in the wall of the pores of 1 / 2 with the cationic dye MB molecules also plays a key role to the superior adsorption capacity of 1 and 2 . In particular, the maximum adsorption capacity of MB, 952 mg g −1 , realized by the calcium MOF 2 , in the present case represents the best result of MB adsorption reported thus far at room temperature by transition‐metal‐based MOFs with the largest value of 902 mg g −1 (Table S3, the Supporting Information), indicating the great potential of the alkaline earth metal‐based MOFs in toxic and carcinogenic organic dye removal application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, MOFs 1 and 2 show much more superior adsorption capacity over MB by about three times that of 3 and 4 in terms of the unit mass of the adsorbent due to the lower atomic weight of Mg/Ca (in 1 / 2 ) in comparison with that of Sr/Ba (in 3 / 4 ). In addition, the electrostatic interaction of nitrogen atoms of porphyrin remained in the wall of the pores of 1 / 2 with the cationic dye MB molecules also plays a key role to the superior adsorption capacity of 1 and 2 . In particular, the maximum adsorption capacity of MB, 952 mg g −1 , realized by the calcium MOF 2 , in the present case represents the best result of MB adsorption reported thus far at room temperature by transition‐metal‐based MOFs with the largest value of 902 mg g −1 (Table S3, the Supporting Information), indicating the great potential of the alkaline earth metal‐based MOFs in toxic and carcinogenic organic dye removal application.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, adsorption of toxic and carcinogenic organic dyes by porous MOFs has received considerable attention in recent years as a simple and effective method for dye removal among various chemical, physical, and biological processes . However, attention in this direction seems to be limited to the transition‐metal‐based MOFs with the highest removal capacity for the typical dye model, methylene blue (MB), of 902 mg g −1 . Investigation over dye adsorption by main group metal including the alkaline earth metal‐based MOFs has not yet reported thus far.…”
Section: Introductionmentioning
confidence: 97%
“…1) show the coordination of BTC and Cu ions. The bands at 1450 and 1649 cm À1 indicate AOACAOA bonding and the bands at 1373 and 1548 cm À1 indicate C@C stretching, demonstrating the incorporation of BTC in the MOF [38,39]. The band at 750 cm À1 is the inorganic finger print, indicating bonding between CuAO.…”
Section: Characterization Of Mofsmentioning
confidence: 91%
“…In the past few years, MOFs have been explored for the adsorption and removal of dyes from aqueous solution, due to their diverse compositions and structure types, large surface area, tunable pore size, and coordinatively unsaturated or saturated metal sites to regulate the adsorption ability [11][12][13][14][15][16][17][18][19]. For example, Jhung et al reported the liquid-phase adsorption of methyl orange over two typical highly porous MIL-101 (MIL = Material of Institute Lavoisier) and MIL-53 and found that the adsorption capacity of MIL-101 was greater than MIL-53, showing the importance of porosity and pore size for the adsorption [11].…”
Section: Introductionmentioning
confidence: 99%